Warts - A Clinicopathological Study - Sen Sumit; Ghosh Sadhan Kumar (Wolters Kluwer Medknow Publications, 2000)
Fifty patients attending an urban skin clinic and suffering from different types of warts were included in this study. Verruca vulgaris was the commonest type of wart comprising 44% of cases and epidermodysplasia verruciformis was the least frequent one. Persons of the age group 16 t o 25 years were mostly affected and majorities were in the middle income group (68.2%). In male, the genital area was the most commonly affected site while in female it was the upper extremity, namely, the fingers, and housewives were predominantly affected. Majority of patients had 2 to 5 lesions of 1 to 2 cm in diameter of 6 months to 1 year duration. Common histopathological features were hyperkeratosis, acanthosis with increased number of vacuolated cells in the stratum malpighii. None showed any sign malignancy.